PENGARUH KOMITMEN DAN IMPLEMENTASI TOTAL QUALITY MANAGEMENT (TQM) TERHADAP KINERJA MANAJERIAL DI KAWASAN INDUSTRI KARAWANG - Puji Isyanto (Jurnal Manajemen dan Bisnis Kreatif, 2019)
This study aims to find the influence of the manager's commitment and implementation of total quality management (TQM) to managerial performance in companies in the industrial area Karawang. This study uses a survey of 158 managers in the company-company industrial area of ​​the city of Karawang. The data used in this study, consisting of primary data obtained through the results of questionnaires and secondary data which supports research that studies literature and journals. Testing hypotheses using path analysis. Based on the results of the study found that: (1). A significant difference between the manager's commitment to the Managerial Performance, (2) There is a significant relationship between Total Quality Management Implementation of the Managerial Performance and (3). A significant difference between commitment and implementation manager of the Total Quality Management Company Operation Manager Performance. Keywords: commitments manager, implementation of TQM, and company operation manager performance